Creating a searchable chromatographic database with the NIST mass spectral search program - Cody, Robert B.; Sparkman, O. David; Moore, Hannah (American Chemical Society (ACS), 2022)
The NIST Mass Spectral Search Program can be used to create a searchable database of chromatograms. This approach was tested for a small database of chromatograms for gin volatiles and for a database of insect cuticular hydrocarbons with retention times and reconstructed total ion current chromatographic peak areas substituted for m/z values and abundance. The In-source HiRes Identity search permitted matching of randomly selected chromatograms against the database with good results. This approach is not intended to replace commercial software for chromatographic database management as it does not address the problems of chromatographic alignment or chromatographic deconvolution, but it does provide a method to manage a simple chromatographic database if other options are not available.